Enhancing Network Performance in Mitigating the Impact of Traffic Accidents with Full User Information - Seyyed Nader Shetab Boushehri; Hossain Poorzahedy; Reza Mahmoudi (Journal of Transportation and Logistics)
This paper presents a novel approach aimed at bolstering network resilience against traffic accidents, particularly when users possess complete information about accident locations. Two new measures are introduced to evaluate the performance of the network and the importance of a link within the network. In addition, an objective function is designed to quantify optimal trip scheduling following an accident that guides investment decisions in network infrastructure. Additionally, we propose a model for addressing the Accident Improvement Problem and put forth a heuristic algorithm to solve this model. To illustrate the feasibility and effectiveness of the proposed methodologies, we present and analyze two illustrative examples, one at a small scale and the other at a medium scale. The findings underscore how the occurrence of accidents can markedly alter the importance of a link within the network during time. Unlike the prevailing trend in existing studies, which often overlook the repercussions of accidents on traffic flow along other links, our research highlights the importance of considering the impact of newcomers on the routes of existing travelers within the network. These findings demonstrate that such considerations can significantly influence the overall performance of the network in the event of an accident.